Pengaruh Strategi Humas dalam Peningkatan Citra Sekolah dan Peningkatan Jumlah Siswa: Studi Kasus SMA Darul Muqorrobin Kota Tangerang - Rahmah, Milyuna; Mirza, Mochammad; Pradesti, Ajeng (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of public relations (PR) strategies on the formation of a school's image and its impact on increasing student enrollment. In an era of growing competition, a school's image has become one of the key factors influencing prospective students and their parents in selecting a school. Effective PR strategies are believed to enhance the school's positive image in the eyes of the public, which, in turn, can lead to an increase in the number of applicants. This research employs a quantitative method with a survey approach, where data is obtained from respondents consisting of current students' parents, prospective students, and school staff. Data analysis is conducted using regression techniques to measure the extent to which PR strategies influence the school's image and contribute to the rise in student enrollment.